Influence of geological factors on coal permeability in the Sihe coal mine - Guangui Zou; Qianhua Zhang; Suping Peng; Jiasheng She; Deliang Teng; Chaochao Jin; Yuyan Che (International Journal of Coal Science & Technology, 2022)
Abstract Permeability of coal reservoirs influence the extraction of coal gas from coal seams. Twelve coal samples were collected at an anticline and a syncline of the No. 3 coal seam in the Sihe coal mine. Porosity, permeability, pore size, vitrinite reflectance, and liquid nitrogen adsorption of the samples were evaluated. Structural curvatures at the sample locations, and the distance between the sampling locations and the nearest faults were calculated based on seismic data. The influences of the evaluated parameters on permeability were analyzed. Major factors that influence permeability of the No. 3 coal seam were extracted using principal component analysis (PCA). Based on the porosity–permeability model derived from the Archie formula and classic Kozeny–Carman equation, we deduced that the permeability of coal increased with an increase in porosity. With an increase in average vitrinite reflectance, permeability decreases first and then increases. PCA results showed that coal permeability was regulated by three key components representing three modes. The first component included pore size, depth, and pore complexity accounting for 52.59% of the variability indicating that it was the most important in controlling permeability. The second component included specific surface area, structural curvature, and porosity, and the third component comprised of specific surface area, porosity, and average vitrinite reflectance. Overall, pore diameter and complexity had significant effects on coal permeability. The results show that researchers and stakeholders must consider the interactions among multiple factors rather than single factors to understand the influences on permeability to facilitate efficient utilization of coalbed methane resources.